PERBEDAAN PRESTASI BELAJAR MAHASISWA ANTARA PEMBELAJARAN KBK DAN PEMBELAJARAN KBI DI STIKES JENDERAL ACHMAD YANIYOGYAKARTA - Iskandar, Rahayu; Susilowati, Latifah; Permatahati, Diah (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Curriculum applied in Indonesia had some changes and perfections, one of them was the change of Content-Based Curriculum or KBI (Kurikulum Berbasis Isi). This curriculum was changed to Competence-Based Curriculum or KBK (Kurikulum Berbasis Kompetensi). KBIis an operational curriculum arrangged, developed and conducted in every education unit that has been ready and able to apply the curriculum, while KBK is a group of plans and managements including the competence and the result of study that should be achieved by the student, scoring system, teaching learning activity and empowerement of the resources. The change of applying curriculum in Indonesia aimed to able the student to work well in national and even international scope. Stikes Jenderal Achmad Yani Yogyakarta had some changes of curriculum from KBI to KBK that applied for students in the academic year of 2014/2015. Whereas, KBI is applied for student in the academic year of 2011/2012 and 2012/2013. KBK impementation affected the students GPA (Grade Point Average). Objective: To study the difference of the students learning achievement who used KBK and KBI in their curriculum in Stikes Jenderal Achmad Yani Yogyakarta. Method: This research was Cross Sectional. The number of the sample were 145 respondents of the nursing students that consisted of students in semester 2, 4, 6, and 8. To analyze the data, the researcher used univariat analysis and bivariat analysis that used t-test independent with p < 0.05 of significance level. Result: There was a significance difference of students’ GPA who applied KBK and KBI (p= .000). The average students’ GPA who used KBIsystem was higher 0.4 than the students who applied KBK system. Conclusion: The difference of applying curriculum in Stikes Jenderal Achmad Yani Yogyakarta affected the differences in GPA. The student who used KBI system obtained higher average than the students who applied KBK system. Keywords: KBK (Competence-Based Curriculum),KBI (Content-Based Curriculum), students learning achievement.